Comparison of security arguments of promising key encapsulation mechanisms - Gorbenko, Yu.I.; Kandii, S.O. (Radiotekhnika, 2022)
The study of key encapsulation mechanisms on algebraic lattices is one of the important directions in modern post-quantum cryptography, since many mechanisms are already either standardized (ANSI X.9.98, DSTU 8961:2019 "Skelya") or are promising candidates for standardization (CRYSTALS-Kyber, FrodoKEM). The purpose of this work is to compare the security arguments of DSTU 8961:2019 "Skelya", CRYSTALS-Kyber, FrodoKEM key encapsulation mechanisms. The paper provides a comparison of theoretical evidence in the idealized random oracle (ROM) and quantum random oracle (QROM) models, as well as a comparison of specific values ​of security parameters in the core-SVP model, which is, in fact, a standard for lattice cryptography. Since all three key encapsulation mechanisms are based on different complex problems (NTRU, Module-LWE, LWE), a comparison of complex lattice theory problems and a comparison of their security arguments are additionally given. The strengths and weaknesses of the considered key encapsulation mechanisms are shown, and areas of research that require more detailed attention are highlighted.